Memaknai Ulang Obyektivitas dalam Media Massa (Sebuah Apresiasi pada Praktik Jurnalisme Subyektif) - edi santoso (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2011)
Objectivity has become the basis for the practice of contemporary journalism. Objectivity has becomea major issue during the last century. However, the ethical debate about objectivity was neverfinished. Even the debate that starts from the definition of objectivity itself, the criteria, until thequestion of pessimism, is it possible there is objectivity in this world? Along with the increasingnumber of criticisms of objective journalism, the idea of subjective journalism increasingly widelyaccepted. Subjective journalism often simply interpreted as journalism in context. That is, journalistsdo not merely present the facts, but also presents the meaning. This paper tries to elaboratethe notion of subjective journalism and explore its relevance in contemporary journalism.